2022
DOI: 10.3390/su14084662
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Barriers of Green Innovation Implementation: Evidence from the Vietnamese Manufacturing Sector

Abstract: Sustainability concerns are rising as an interesting topic in both academia and industry. Many scholars revealed that green innovation is an excellent solution to enable organizations to achieve various benefits, such as enhancing their reputation and competitive advantages. Thus, this is the first study in Vietnam to consider the barriers to implementing green innovation. The research aims to identify the obstacles to green innovation practices in the Vietnamese manufacturing sector. The interpretive structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Every organization faces a complex business environment and competition [1,2]. Several factors may cause an organization to transform immediately, including competition between organizations [3,4] and a shorter product life cycle [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Every organization faces a complex business environment and competition [1,2]. Several factors may cause an organization to transform immediately, including competition between organizations [3,4] and a shorter product life cycle [5].…”
Section: Introductionmentioning
confidence: 99%
“…Top managers have an essential role in creating ambidexterity [2,13]; several studies have documented that social networks help managers and companies prioritize positions to obtain information for the purposes of exploitation and exploration [14][15][16]. The concept of managerial social capital can be used to explain how top managers access and mobilize the dual knowledge required for ambidexterity [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Huang et al [27] revealed that there are several obstacles that can occur in efforts to adopt Green Innovation in SMEs. These include lack of courses or training in conducting Green Innovation, lack of knowledge related to environmental issues, lack of cooperation in partnerships, and lack of customer demand for environmentally friendly products.…”
Section: Inhibitors Green Innovation In Smesmentioning
confidence: 99%